Extracorporeal photopheresis in steroid-refractory chronic graft-versus-host disease: A retrospective multicenter study. (October 2021) - Dal, Mehmet Sinan; Batgi, Hikmettullah; Erkurt, Mehmet Ali; Hindilerden, Ipek Yonal; Kuku, Irfan; Kurtoglu, Erdal; Kaya, Emin; Besisik, Sevgi Kalayoglu; Berber, Ilhami; Nalcaci, Meliha; Ulas, Turgay; Altuntas, Fevzi
Abstract: Background and objectives: Extracorporeal photopheresis (ECP) is a treatment strategy in steroid-refractory chronic graft-versus-host disease (cGvHD). In this study, we aimed to share our multicenter experience using ECP in our steroid-refractory cGvHD patients. Materials and methods: In this multicenter observational retrospective study with the participation of four Turkish transplant centers, 100 patients with the diagnosis of steroid-refractory cGvHD who underwent ECP were analyzed. All ECP procedures were performed with the off-line system. Results: Severe cGvHD was observed in 77 % of the patients. 50 % of the patients had more than 1 organ involvement. The overall response rate in cGvHD was 58 %, and the complete response (CR) rate was 35 %. The skin was the most involved organ, with a response rate of 61.2 % (CR rate 30.6 %) in cGvHD. At a median 13 months (1−261) follow-up, overall survival (OS) was 41 % (n = 41) and the mortality rate was 59 % (n = 59). Median overall survival (OS) was 2 months for non-responders and 91 months for responders (p < 0.001). Significant OS differences were observed for patients responding to ECP in cGvHD (HR = 4.1, p = 0.001) patients. Conclusions: ECP is a good therapeutic alternative and could be used earlier in patients with steroid-resistant cGvHD.